Mental health and headaches in university professors - Sperandio, Ana Beatriz Batáglia; Rodrigues, André Soares; Queiroz, Bruno Seabra; Souza, Jadde Inhã Lisboa de; Fontes, Júlia Lucato; Comisso, Laura Beatriz Maciel; Lima, Liara Ruiz; Melhado, Eliana Meire (Headache Medicine, 2024)
Introduction There is a lot of discussion about the world's quality of life, mental health, disease improvement standards according to the WHO, and so many actions and attitudes in a movement to improve life, in addition to life expectancy. Objectives To determine the mental health status of university medical professors at Unifipa. emphasizing the relation between headache disabling and depression and anxiety’scores. Methodology Cross-sectional cohort in a single intervention, which consisted of responding to a health and quality of life questionnaire, focusing on mental health, and in this report, headaches. Results Participants’ number was 46. About 51% were between 31 and 40 years old; 56.5% were women, 67.4% were married or in a stable union, 21.7% had a master's degree and 26.1% had a PHD. Regarding mental health, it was noted that professors with severe depression showed the presence of a moderate or severe level of anxiety, while those with minimal depression showed a low level of anxiety. Regarding to the headaches, it was observed that HIT-test scores above 50 correlated more with higher depression and anxiety scores and lower HIT-test scores correlated with lower depression and anxiety scores. Conclusion Research is important to evaluate the university professors’ mental health and predict actions that can be taken to improve it. And headaches cause disabling when associated to depression and anxiety. We conclude that headache’s burden can related to worsening depression and anxiety’scores, even though not significantly.